Enterobiasis-related inflammatory caecal polyp masquerading as a malignancy. (15th January 2014) - Elsaid, Nada; Mahmood, Humza; Tekkis, Paris; Tan, Emile
Summary: A 55 -year-old Asian man was seen in the emergency department with bleeding per rectum. He was a teetotaller and had no previous abdominal surgery. He did, however, report a change in bowel habit towards constipation. He underwent colonoscopy which revealed a lesion, highly suspicious of malignancy, in the caecum. On review by two consultants, a decision to completely resect this lesion was made. Histological analysis of the polypoidal growth showed it to be a consequence of chronic infection with the helminth Enterobius vermicularis . Importantly, there was no evidence of dysplastic or malignant cells. The patient was subsequently discharged with a 3-day course of antihelminthic mebendazole and reassured that his per rectal bleeding was most likely due to haemorrhoids discovered at rectal examination.